2015
DOI: 10.1021/acs.joc.5b01824
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ketones through Microwave Irradiation Promoted Metal-Free Alkylation of Aldehydes by Activation of C(sp3)–H Bond

Abstract: In this paper, a novel methodology for the synthesis of ketones via microwave irradiation promoted direct alkylation of aldehydes by activation of the inert C(sp(3))-H bond has been developed. Notably, the reactions were accomplished under metal-free conditions and used commercially available aldehydes and cycloalkanes as substrates without prefunctionalization. By using this novel method, an alternative synthetic approach toward the key intermediates for the preparation of the pharmaceutically valuable oxaspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Interestingly, the reaction proceeded smoothly although only 5 equiv of cyclohexane was employed. Typically, significantly higher substrate concentrations were required in similar reactions that allow for directly functionalizing C(sp 3 )−H bonds . Reasonable yields of 48 % and 60 % could be obtained even with 2 or 3 equiv of the C−H coupling partner, respectively (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the reaction proceeded smoothly although only 5 equiv of cyclohexane was employed. Typically, significantly higher substrate concentrations were required in similar reactions that allow for directly functionalizing C(sp 3 )−H bonds . Reasonable yields of 48 % and 60 % could be obtained even with 2 or 3 equiv of the C−H coupling partner, respectively (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…This work represents the first case of successful C(sp 3 )−H functionalization with amides as a user‐friendly acyl surrogate and a rare example of applying photoredox catalysis in conjunction with amide activation, thus breaking the boundaries of both reaction modes. Namely, a significantly challenging cross‐coupling reaction between two inert functional groups is achieved under exceptionally mild conditions furnishing valuable ketones as products without using any external oxidant . Notably, a novel substrate‐assisted reaction mechanism, which commences with the aliphatic C−H activation prior to the commonly expected Ni 0/II oxidative addition, derived from the synergistic effect of the reactivity difference between amides and aliphatic C−H bonds, is disclosed leading to a highly productive reaction pathway for the less reactive N‐acylsuccinimides compared to other more activated, conventional acyl sources such as acyl chlorides or anhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Although various routes for ketone synthesis have been reported, most require relatively expensive starting materials, such as organic halides and organometallic reagents. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] We recently reported the coupling of aldehydes and non-activated hydrocarbons using CrCl 3 (3 eq.) 20) and tetrabutylammonium decatungstate (TBADT; 10 mol%) (Chart 1a).…”
Section: Introductionmentioning
confidence: 99%
“…diversity are still needed. Inspired by those pioneering studies and as ac ontinuation of our recenti nterest in the radical transformation of aldehydes, [10] we have developed an alternative synthesis of esters through the oxidative esterification of aldehydes with alkyl halides [11] under the promotion of tBuOOH and Bu 4 NI. From this reaction,e sters with broad structural diversity were efficiently prepared [Scheme 1, Eq.…”
mentioning
confidence: 99%
“…Meanwhile, it was also observed that increasing the amount of Bu 4 NI from 0.2 equivalents to 1equivalent could improvet he efficiencys ignificantly (entries3, 5 -7). Further studies showedt hat Bu 4 NBr,K I, I 2 ,a nd CuI were ineffective as catalysts for the formation of 3a (entries [8][9][10][11]. When H 2 O 2 was employed as ap ossible oxidant to replace tBuOOH, the formation of 3a was not observed (entry 12).…”
mentioning
confidence: 99%